„Et grønt Horehuus“. Kongens Have som skændslens sted i trykkefrihedsskrifterne 1771-73 - Langen, Ulrik (Historisk Tidsskrift, 2017)
"A green brothel" – The King's Garden (Kongens Have) as a place of infamy in the Press Freedom Writings 1771–1773 This article explores how certain aspects of urban life in Copenhagen during the Struensee regime (1770–1772) were presented in some of the so-called Press Freedom Writings. These semi-fictional descriptions of the unrestrained sociability in The King’s Garden (Kongens Have) was a significant part of the severe criticism faced by the Struensee regime. During the summer of 1771, attacks on the ordinances drawn up by Struensee became more evident, and the decrees regarding chastity and public morals were especially emblematic of what was regarded as a corrupt government led by an adulterer. During the second half of the 18th Century, public gardens and promenades were considered essential to the maintenance of public life and urban civility of any enlightened European city, also in Copenhagen where The King’s Garden played a central role. Anonymous writers criticized what they interpreted as a challenge to the traditional social norms of conduct in the garden. The presumed sexual debauchery in the garden was seen as undermining this ideal space of civil sociability. The blame for this decay was aimed at Struensee by asserting a direct connection between the legislation on public morals and the government’s legitimation of the unrestricted popular, not to say immoral and obscene, uses of the garden. In the article, the Press Freedom Writings are analyzed as reflections of the emergence of a new public sphere, which developed in the wake of the Ordinance of Press Freedom of 14 September 1770. On the one hand, the writings presume to reflect a certain public practice; on the other, they represent a moral discourse central to many of the Press Freedom Writings. The study emphasizes the impossibility of keeping these features apart.